2004
DOI: 10.1002/cncr.20451
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine-needle aspiration biopsy: A powerful tool to obtain samples from small lesions

Abstract: BACKGROUND Endoscopic ultrasound (EUS) is a powerful imaging modality to identify and determine the extent of a lesion. In addition, EUS is superior to a computed tomography scan in detecting lesions < 3 cm. The objective of the current study was to determine whether small lesions (≤ 25 mm) affected the specimen adequacy and the diagnostic accuracy for lesions aspirated under EUS guidance. METHODS In the current study, 209 consecutive EUS‐guided fine‐needle aspiration biopsy (EUS‐FNAB) samples ≤ 25 mm (100 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 35 publications
3
113
1
2
Order By: Relevance
“…Contrary to what might be expected, the size of the lesions, whether small ( 25 mm) or large (>25 mm) does not influence the overall diagnostic yield, sensitivity, specificity, or accuracy of the method. 120 Several studies have assessed EUS-FNA receiver operating characteristics by including only pancreatic cancer patients. [121][122][123][124][125][126][127][128][129][130][131][132] The initial reports showed a sensitivity of 85-95%, with a specificity close to 100%.…”
Section: Eus-fnamentioning
confidence: 99%
“…Contrary to what might be expected, the size of the lesions, whether small ( 25 mm) or large (>25 mm) does not influence the overall diagnostic yield, sensitivity, specificity, or accuracy of the method. 120 Several studies have assessed EUS-FNA receiver operating characteristics by including only pancreatic cancer patients. [121][122][123][124][125][126][127][128][129][130][131][132] The initial reports showed a sensitivity of 85-95%, with a specificity close to 100%.…”
Section: Eus-fnamentioning
confidence: 99%
“…6,7 The pancreas remains 1 of the most commonly aspirated sites using this modality. This high degree of accuracy is achieved through understanding the key cytologic features of the various pancreatic lesions, which have been previously documented in the literature.…”
mentioning
confidence: 99%
“…It has proven to be a valuable tool in the preoperative diagnosis and management of patients with pancreatic lesions. [1][2][3][4][5][6] Whereas most aspirations yield diagnostic material, the differential diagnosis of the reactive/reparative and neoplastic processes as well as their precise classification in the pancreatic EUS-FNAs specimens can be challenging. This can be explained by the considerable overlap in the cytomorphologic features of these processes in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Ductal adenocarcinoma is the most common malignancy of the pancreas. 7 Recently, it has been shown that the malignant transformation of pancreatic ductal epithelium changes the epithelial expression of apomucins.…”
mentioning
confidence: 99%